Periodic two-dimensional self reinforced polypropylene honeycomb core for sandwich structures - Rejab, Mohd Ruzaimi Mat (2017)
Hexagonal honeycomb cores have found extensive applications particularly in the aerospace and naval industries. In view of the recent interest in novel strong and lightweight core architectures, square honeycomb cores were manufactured and tested under uniform lateral compression. A slotting technique has been used to manufacture the square honeycomb self-reinforced polypropylene (SRPP). The compressive responses of the sandwich structures were measured as a function of relative density. In this research, particular focus is placed on examining the compression strength and energy absorption characteristics of the square honeycombs with different types of model. Comparisons in terms of specific strength and specific energy absorption have shown that the Sandwich Star core offers excellent properties in term of compressive strength. The SRPP core could potentially be used as an alternative lightweight core material for recyclable sandwich structures.